Influence of egg card color preference, inoculation time, generational succession, and learning experience on the parasitism of Trichogramma ostriniae - Huixian Wang; Wenya Zhu; Ruifeng Guo; Ye Zhang (PLoS ONE, 2025)
This study investigated the parasitic selection preferences of female Trichogramma ostriniae on egg cards of different colors, considering the effects of inoculation time, generations, and learning experiences on wasp parasitism. The preferences of female T. ostriniae for oviposition were assessed across egg cards of different colors. Subsequent experiments identified the egg card background color most preferred by T. ostriniae and examined the influence of inoculation time, generations, and learning experiences on parasitism rates. The findings revealed a significant preference for T. ostriniae for yellow egg cards compared to other colors, with the highest parasitism rate observed on yellow and the lowest on red. Inoculation time had a significant effect on the parasitism of T. ostriniae on yellow egg cards, with the highest parasitism observed at 16h post-inoculation and a noticeable negative linear correlation with increasing inoculation time up to 48h (F = 8.73, P<0.05). The number of generations did not significantly affect the parasitism rate of T. ostriniae on yellow egg cards, nor did the learning experiences show a significant difference in the relative parasitism of T. ostriniae on yellow egg cards among the learning experiences. However, T. ostriniae had a significantly higher parasitization rate on yellow egg cards compared to white egg cards, regardless of generation or learning experience. Those results showed that female T. ostriniae strongly prefers yellow. The highest parasitism of female T. ostriniae on yellow egg cards was observed at 16h post-inoculation.